Finishing properties of Japanese table from (neolamarckia cadamba) / Athirah Razak - Razak, Athirah (2014)
Wood finishes give a desired appearance, protect wood surfaces, and provide a cleanable surface. The finishing material depends on the type of wood and the used of the furniture. In this study, a wood species kelempayan (Neolamarckia cadamba) was used as a sample. Acid catalyst lacquer as the finishing material were use to carried out the suitability of wood finish for applied on Japanese table. The aims of the study were to determine the finishing properties of kelempayan (Neolamarckia cadamba) by using different finishing system (system A and system B), where system A (sealer + topcoat) and system B (topcoat). From this study, the finishing properties were identifying through pencil hardness test, adhesion test (cross cut test), surface roughness test and household test. As a result system A gave better performance than system B on finishing testing and suitable use on the furniture.